(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Unfortunately, many UTIs in the newborn period do not have a specific clinical picture and diagnosis of TORCH-infections only by clinical manifestations (without involving specific microbiological studies) leads to diagnostic errors in 90-95% of cases. The diagnosis of UTI is substantiated by the totality of: - anamnestic, - clinical - laboratory data [20,21,22,23].